Psychiatric comorbidity and suicidal ideation in psoriasis, melanoma and allergic disorders. (3rd July 2017) - Pompili, Maurizio; Innamorati, Marco; Forte, Alberto; Erbuto, Denise; Lamis, Dorian A.; Narcisi, Alessandra; Rea, Claudia; Orsini, Diego; D'Arino, Andrea; Arcese, Annalisa; Bellini, Samantha; Trovarelli, Sara; et al.
Abstract: Objective: Psychiatric disorders and suicide risk (especially in psoriasis) are frequent and disabling conditions in patients with skin diseases. The aim of this study was to examine the risk of suicide and stressful life events in a sample of patients with skin disease. Methods: A sample of 242 dermatological patients (142 women and 100 men), 112 of which had psoriasis, 77 had melanoma, and 53 were suffering with chronic allergic diseases. Patients were administered the MINI International Neuropsychiatric Interview (MINI), Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), and the Columbia-Suicide Severity Rating Scale (C-SSRS). Patients were also asked about their experiences with stressful life events. Results: Patients with psoriasis were more likely to have a history of psychiatric disorders (36.6% vs. 13.2% χ 2 (1)  = 9.55; p  = 0.002) compared to patients with allergies. Specifically, patients with psoriasis more likely had a diagnosis of a mood disorder (16.1% vs. 3.9% χ 2 (1)  = 6.85; p  = 0.009; 16.1% vs. 0% χ 2 (1)  = 9.56; p  = 0.002) and reported past suicidal ideation (33.9% vs. 15.6% χ 2 (1)  = 7.89; p  = 0.005; 33.9% vs. 18.9% χ 2 (1)  = 3.96; p  = 0.047) as compared to those with melanoma and allergy. Conclusions: The results from this study suggest that patients affected by psoriasis have an increased risk of psychiatric comorbidities and suicidal ideation compared to those who have other dermatological disorders.